Different genotype and a liquid whey-supplemented diet influence the resilience of pigs through immune-modulation and anti-inflammatory response - D'Alessandro, Enrico; Arfuso, Francesca; Floridia, Viviana; Tardiolo, Giuseppe; Fazio, Francesco; Giannetto, Claudia; Piccione, Giuseppe; Zumbo, Alessandro (Frontiers in Veterinary Science, 2022)
This study evaluated (i) whether weight gain and levels of inflammatory and immune markers including white blood cells (WBC), serum haptoglobin, C-reactive protein, albumin, globulin fractions change between the Nero Siciliano pigs breed and the crossbreed white pigs reared under the same environmental and farming conditions; (ii) whether a liquid whey diet supplementation affects the investigated parameters in both breeds. In this study, 10 crossbreed white pigs and 10 Nero Siciliano pigs were given control feed representing the control groups (CTRC and CTRNS), whereas 10 crossbreed and 10 Nero Siciliano pigs were given control feed supplemented with liquid whey for 2 months representing the experimental groups (WC and WNS). From each pig body weight and blood were collected before experimental diet supplementation (T0), and one (T1) and two (T2) months after the starting of diet supplemented with whey. White blood cell count (WBC), serum haptoglobin, C-reactive protein, total proteins, albumin and globulin fraction concentration were assessed. Two-way analysis of variance showed an increasing trend of body weight both in control and experimental groups of the two pig breeds throughout the monitoring period (p < 0.01) without a significant effect of breed and diet (p > 0.05). Haptoglobin, β1- and β2-globulins was affected by pig breed, diet supplementation and time (p < 0.01). WBC, C-reactive protein, albumin, α-globulins and A/G ratio resulted affected by diet supplementation (p < 0.01) and time (p < 0.01) without an influence of breed (p > 0.05). Nero Siciliano pigs showed lower levels of haptoglobin, β1- and β2-globulins compared to crossbreed white pigs. Nero Siciliano pigs and crossbreed white pigs fed with liquid whey showed lower levels of WBC, haptoglobin, C-reactive protein, α-, β1- and β2-globulins and higher values of albumin compared to control groups. Results reinforced the hypothesis that autochthonous breeds possess higher resilience to farming conditions when compared to allochthonous breeds. Moreover, an immune-modulatory and an anti-inflammatory power of liquid whey dietary supplementation is suggested probably thanks to its content in natural bioactive substances including anti-inflammatory cytokines and antioxidative factors.